2019
DOI: 10.14738/assrj.65.6385
|View full text |Cite
|
Sign up to set email alerts
|

Achievement Motivation And Emotional Intelligence As Predictors Of Mathematical Resilience Among Secondary School Students

Abstract: This study investigated achievement motivation and emotional intelligence as predictors of Mathematical resilience among senior secondary school students in Rivers Nigeria. Two research questions were answered and two hypotheses were tested at 0.05 alpha level. The population of the study comprised all 24,727 senior secondary school (SS2) students in the 247 public secondary schools in Rivers State. Sample size of 1690 was obtained using 20% of the population in simple random sampling technique. Three self-des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
1
4
0
2
Order By: Relevance
“…This finding holds great importance, especially in light of Cropp's (2017) study that showed the efficacy of peer interventions in diminishing anxiety levels, thereby potentially enhance MR. Johnston-Wilder et al ( 2021) connect self-determination theory to MR promotion, highlighting the need for a supportive and independent atmosphere for students. This aligns with the positive correlations found between motivation, metacognitive strategies, and MR in several studies (Afriyanti et al, 2018;Joy & Obiagaeri, 2019;Trigueros et al, 2020). Nevertheless, Faradillah & Wulandari (2021a) posits that this correlation may not follow a linear pattern, depending on individual differences or contextual factors.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 89%
“…This finding holds great importance, especially in light of Cropp's (2017) study that showed the efficacy of peer interventions in diminishing anxiety levels, thereby potentially enhance MR. Johnston-Wilder et al ( 2021) connect self-determination theory to MR promotion, highlighting the need for a supportive and independent atmosphere for students. This aligns with the positive correlations found between motivation, metacognitive strategies, and MR in several studies (Afriyanti et al, 2018;Joy & Obiagaeri, 2019;Trigueros et al, 2020). Nevertheless, Faradillah & Wulandari (2021a) posits that this correlation may not follow a linear pattern, depending on individual differences or contextual factors.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 89%
“…Low emotional intelligence can lead to stress levels with high acculturation and usually procrastination so that student achievement can be hampered (Prentice et al, 2020;Fteiha & Awwad, 2020;Tam et al, 2021). The way students think is related to their emotional intelligence (Joy, 2019;Nugroho et al, 2019). To achieve good academic performance, students need to be assisted to be able to acquire strong emotional and mental skills in facing various challenges (Jan & Anwar, 2019;MacCann et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Soal selidik yang digunakan menggunakan skala likert dengan lima mata (Attami et al, 2020;Harsela & Asih, 2020) dan skala likert empat mata (Findik, 2016;Id et al, 2019). Kajian mendapati penyelidik merujuk dan mengubah suai jenis skala bagi daya tahan seperti Mathematical Resilience Scale (MRS) (Gü 2018 ;Joy 2019). Penggunaan instrumen yang telah kukuh dapat memberi panduan kepada penyelidik bagi mengubah suai item mengikut kesesuaian populasi kaji supaya alat tersebut dapat mengukur apa yang sepatutnya diukur.…”
Section: Instrumen Kajianunclassified
“…Guru perlu melakukan perubahan seperti pemilihan blended learning agar dapat meningkatkan ketahanan pelajar. perkara ini dapat menambah baik pencapaian akademik, memberi motivasi dan kestabilan emosi semasa mempelajari matematik (Fitri et al, 2019;Joy, 2019;Laelasari et al, 2019a).…”
Section: Perbincangan Kajianunclassified